Integrating Educational Management Dimensions into Social Entrepreneurship Models: Empowering Housewives through Hand-Woven MSMEs in Poto Village - Rudi Susanto; Fendy Maradita (Journal of Educational Management Research, 2025)
This study analyzes social entrepreneurship business models in empowering housewives through hand-woven micro, small, and medium enterprises (MSMEs) in Poto Village, integrating educational management dimensions in community-based economic activities. A qualitative approach was applied, with informants selected using the snowball sampling technique. Data were collected through in-depth interviews, observations, and documentation, and analyzed using the Miles and Huberman interactive model, including data reduction, display, and conclusion drawing. Findings show that the Poto Village weaving business model has a strong social entrepreneurship orientation, with women weavers actively contributing to household income and cultural preservation. Key value propositions include authentic traditional motifs, gold threads, crystals, and a manual production process passed down through generations. Customer relationships remain trust-based, marketing relies on direct sales and word-of-mouth, and formal partnerships with government and digital platforms are limited. From an educational management perspective, empowerment involves planning, organizing, implementation, and evaluation through training, mentoring, and skill development. The Triple Layer Business Model Canvas analysis highlights increased income, women’s economic independence, social cohesion, and cultural sustainability. Integrating educational management dimensions into social entrepreneurship can enhance the sustainability and transformative impact of community-based MSMEs.